Rewrite the equation by completing the square.
x^2 + 7x + 12 = 0
2 answers:
Answer:
(x + )² - = 0
Step-by-step explanation:
Given
x² + 7x + 12 = 0
To complete the square
add/subtract ( half the coefficient of the x- term)² to x² + 7x
x² + 2( )x + - + 12 = 0
(x + )² - + = 0 , that is
(x + )² - = 0
Answer:
x^2 + 7x + 12 = 0
x^2 + 7x = -12
(+3)(+4)=0
=−3
=−4
I also love r o blox
Hope This Helps!!!
You might be interested in
2a + b - 3
2(5) + 2 - 3
10 + 2 - 3
12 - 3 = 9
Answer - 9
Hope this Helps!!
Answer:
a) 75/3=25/1
Step-by-step explanation:
Answer:
A
Step-by-step explanation:
it is y=-1/2x-4 for sure.